Oxidative Balance Scores (OBSs) Integrating Nutrient, Food and Lifestyle Dimensions: Development of the NutrientL-OBS and FoodL-OBS - Ángela Hernández-Ruiz; Belén García-Villanova; Eduardo J. Guerra-Hernández; Cayetano Javier Carrión-García; Pilar Amiano; María-José Sánchez; Esther Molina-Montes (Antioxidants, 2022)
Oxidative Balance Scores (OBS) are tools that allow us to assess the individual’s antioxidant state by ranking both antioxidant and pro-oxidant components of dietary and lifestyle factors. Our aim was to develop novel OBSs accounting for either the global supply of nutrient antioxidants in the diet, or the intake of antioxidant-rich foods, in combination with lifestyle factors. Pro-oxidant factors were also considered. Within two centers of the Spanish European Prospective Investigation into Cancer and Nutrition (EPIC) study, EPIC-Granada and EPIC-Gipuzkoa (N = 14,756 participants), we developed the Nurient, Food and Lifestyle OBS (NutrientL-OBS and FoodL-OBS), and their simplified versions (solely with dietary or lifestyle factors, the Nutrient-OBS, Food-OBS and L-OBS). Their antioxidant potential was evaluated considering their relationship with: (i) 20 scores of adherence to the Mediterranean Diet (MD); and, (ii) 25 biomarkers of antioxidant nutrients (ascorbic acid, β-carotene, etc.), inflammation (CRP, TNF-alpha, etc.) and oxidative stress (uric acid), among 210 participants. Spearman correlation and multivariate linear regression analyses were applied to analyze these associations. Some statistically significant relationships were encountered between the NutrientL-OBS and the FoodL-OBS with the MD scores, and with ascorbic acid (per one-unit increase in OBS: β = 0.012 and 0.015; p = 0.022 and 0.008, respectively) and CRP (per one-unit increase in both OBS: β = −0.02; p = 0.02); the latter appeared to be restricted to the OBS´s lifestyle components. In conclusion, the NutrientL- and FoodL-OBSs and their sub-versions are related to antioxidant-rich dietary patterns and to biomarkers of antioxidant nutrient intake and inflammation, supporting that these tools are valid to assess the individual´s oxidative/antioxidant status.